Opini Peserta terhadap Transparansi Penerimaan CPNS melalui Metode Computer Assisted Test (CAT) - Sulaiman Sulaiman; Dody Radiansah (Eksos, 2021)
This study aims to determine the opinion of participants on the level of transparency of the selection of CPNS acceptance through the CAT method at the Bengkayang Regency Regional Personnel Agency. The research location is in Bengkayang Regency. This type of research is a survey method with a quantitative approach. Data were analyzed by descriptive statistics. Descriptive statistics describe participants' opinions on the level of transparency in the selection of candidates for civil servants through the CAT method. The population in this study were all participants who took part in the selection of CPNS acceptance at the Bengkayang Regency Regional Personnel Agency in 2020. Sampling was carried out by stratified random sampling with a sample of 41 people. The results showed that the participants' opinions on the level of transparency of the selection of CPNS admissions through the CAT method for each dimension on average were in the good and very good categories; so this shows that the opinion of participants on the level of transparency of the selection of CPNS acceptance through the CAT method at the Bengkayang Regency Regional Personnel Agency is very positive.